Legal Mechanism of Venture Capital Cooperation for Small and Medium Enterprises at the Regional Level - Silaen, Jonner Binton (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The government faces funding challenges for micro, small, and medium enterprises (MSMEs) due to collateral limitations in financing, requiring appropriate financing solutions. One such solution is venture capital, a long-term investment based on profit rather than interest or dividends. This study analyzes venture capital management in Indonesia and the regulations supporting its development, especially for MSMEs and the creative sector. The research uses a normative juridical approach with qualitative analysis of legal materials from primary, secondary, and tertiary sources. The findings reveal two approaches to venture capital management: the One-Tier Approach and the Two-Tier Approach. No legal distinction between management and venture capital in Indonesia allows for flexible management. Venture capital is regulated by Law No. 40 of 2007 on Limited Liability Companies and other related regulations. The implications of this study highlight the need for legal reforms to support venture capital’s role in financing businesses, along with closer cooperation between the Financial Services Authority (OJK), relevant ministries, and other stakeholders, with political support from the DPR to accelerate MSME and creative sector development.